Computational intelligence, communications, and business analytics. first International Conference, CICBA 2017, Kolkata, India, March 24-25, 2017, Revised selected papers /: first International Conference, CICBA 2017, Kolkata, India, March 24-25, 2017, Revised selected papers. Part I : (2017) - Unknown
No abstract available